Designer α1,6-Fucosidase Mutants Enable Direct Core Fucosylation of Intact N-Glycopeptides and N-Glycoproteins - Li, Chao (J Am Chem Soc, 2017)
Core fucosylation of N-glycoproteins plays a crucial role in modulating the biological functions of glycoproteins. Yet, the synthesis of structurally well-defined, core-fucosylated glycoproteins remains a challenging task due to the complexity in multi-step chemical synthesis or the inability of the biosynthetic α1,6-fucosyltransferase (FUT8) to directly fucosylate full-size mature N-glycans in a chemoenzymatic approach. We report in this paper the design and generation of potential α1,6-fucosynthase and fucoligase for direct core-fucosylation of intact N-glycoproteins. We found that mutation at the nucleophilic residue (D200) did not provide a typical glycosynthase from this bacterial enzyme, but several mutants with mutation at the general acid/base residue E274 of the Lactobacillus casei α1,6-fucosidase, including E274A, E274S, and E274G, acted as efficient glycoligases that could fucosylate a wide variety of complex N-glycopeptides and intact glycoproteins by using α-fucosyl fluoride as a simple donor substrate. Studies on the substrate specificity revealed that the α1,6-fucosidase mutants could introduce an α1,6-fucose moiety specifically at the Asn-linked GlcNAc moiety not only to GlcNAc-peptide, but also to high-mannose and complex type N-glycans in the context of N-glycopeptides, N-glycoproteins, and intact antibodies. This discovery opens a new avenue to a wide variety of homogeneous, core-fucosylated N-glycopeptides and N-glycoproteins that are hitherto difficult to obtain for structural and functional studies.